The Historical Roots of the Image of Timurid Princesses (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the place of the glorious Great Timur of Turan and Timurid princesses in historical works and fiction. Interesting information is provided about the position of Timurid princesses in the Timurid empire. The article uses the necessary literature.